2008
DOI: 10.1002/cbm.711
|View full text |Cite
|
Sign up to set email alerts
|

Changes over time in homicides by women: a register‐based study comparing female offenders from 1982 to 1992 and 1993 to 2005

Abstract: In Finland, there have been changes in characteristics of women who commit homicide and their crimes over time, with the apparent development of a subgroup of women who kill who are much more like men who kill than women in the 1980s and early 1990s. Preventing substance abuse and marginalization are likely to be important ways of preventing homicide by both female and male perpetrators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…More specifically, a knife was the most commonly used weapon in filicides (26.67%), parricides (75%), homicides (37.50%) and domestic murders (25%). This finding supports extant research that women tend to use an object that is close at hand (such as a knife or a weapon that causes blunt trauma) when committing a murder (Cole et al, 1968;Putkonen, Collander et al, 2001;Putkonen, Weizmann-Henelius et al, 2008). However, it diverges in that a knife rather than a gun was the most commonly used weapon in the parricides (Johnson-Smith, 2004;Starek, 2003).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…More specifically, a knife was the most commonly used weapon in filicides (26.67%), parricides (75%), homicides (37.50%) and domestic murders (25%). This finding supports extant research that women tend to use an object that is close at hand (such as a knife or a weapon that causes blunt trauma) when committing a murder (Cole et al, 1968;Putkonen, Collander et al, 2001;Putkonen, Weizmann-Henelius et al, 2008). However, it diverges in that a knife rather than a gun was the most commonly used weapon in the parricides (Johnson-Smith, 2004;Starek, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…Women, like men, may kill for various reasons: perceived threat and self-defence (Kandalepas, 2011;Seletswane, 2007), personal gain (Hickey, 2003(Hickey, , 2010, poverty (Jensen, 2001;Schwartz, 2012), predatory reasons (Hickey, 2003(Hickey, , 2010, mental pathology (McKee, Shea, Mogy, & Holden, 2001) and due to the influence of substances (Goetting, 1989;Putkonen, Collander, Honkasalo, & Lönnqvist, 2001;Putkonen, Weizmann-Henelius, Lindberg, Rovamo, & Häkkänen, 2008).…”
mentioning
confidence: 98%
“…They were also more likely to be presently victims of physical, psychological and sexual abuse, as well as childhood physical, psychological and sexual abuse. They showed also elevated levels of substances abuse, and were more frequently suffering from physical and mental illness [3,5,7,11,18,23]. Yourstone [21] established that female offenders were less likely to be foreign nationals than male offenders.…”
Section: Introductionmentioning
confidence: 99%
“…The family characteristics of the child have an impact on the child's future behaviors and attitudes (Çelen, 2007). Studies showed that female offenders experienced a high rate of physical, emotional and sexual trauma in their childhood (Rossegger et al, 2009;Steffensmeier & Broidy, 2001;Weizmann-Henelius et al, 2003;Putkonen et al, 2008). As it is known, individuals who are abused in their family are most likely to continue with this cycle of abuse in their adult relationships (Grotevan, et al, 2006;Lansford, et al, 2007;Wolfe, et al, 2004;Widom & White, Akduman, İ., Çelik, D., & Tiftik, N. (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Women who are physically abused in their childhood and those who witnessed domestic violence were found to have a higher risk of behaving aggressively towards their partners (Milletich, Kelley, Doane & Pearson, 2010). On the relationship between female criminality and childhood trauma, studies show that there is a high ratio of childhood physical, emotional and sexual abuse experiences of female criminals (Steffensmeier & Broidy, 2001;Weizmann-Henelius, Viemero & Eronen, 2003;Weizmann-Henelius, 2006;Putkonen, Weizmann-Henelius, Lindberg, Rovamo & Hakkanen, 2008;Rossegger, Wetli, Urbanioki, Elbert, Cartoni & Endrassi, 2009). When the reasons behind these aggressive behaviors and anger is studied, it was suggested that they might be the manifestation of the loss of control, feelings of helplessness and frustration that the child .…”
Section: Introductionmentioning
confidence: 99%